PO066 Alterations in attention, fatigue and alertness associated with the premonitory and postdrome stages of triggered migraine attacks. (1st December 2017) - Karsan, Nazia; Bose, Pyari; Thompson, Charlotte; Goadsby, Peter
Abstract : Despite increasing awareness that non-painful symptoms can manifest at any time during a migraine attack, there is little quantitative evidence to support the severity of such symptoms. We aimed to understand the differences in fatigue (Daily Fatigue Impact Scale- DFIS), attention (Sustained Attention to Response Task- SART) and alertness (Karolinska Sleepiness Scale- KSS) at baseline and during the premonitory and postdrome stages of nitroglycerin-triggered migraine attacks, using validated psychological tests. Baseline (symptom free) scores for all tests for each subject (n=16) were collected prior to any drug administration. The same tests were conducted in the premonitory (n=7) or postdrome (n=9) phases of triggered attacks, following display of symptoms after nitroglycerin infusion and when appropriate, after effective headache treatment. Statistical analyses were performed using the paired t -test. p<0.05 was considered significant. There were statistically significant increases in scores on the KSS and DFIS in the premonitory and postdrome stages compared to baseline. No statistically significant differences in SART scores in either phase were observed compared to baseline. Despite a small sample size, we have demonstrated notable changes in alertness and fatigue in the premonitory and postdrome stages of a migraine attack. This is an area that warrants increased clinical and research attention.